Ekstensifikasi Peran Lembaga Jasa Keuangan Dalam Pencapaian SDGs Di Kawasan Bandara Dhoho Kediri - Affandi, Yorinal; Askafi, Eka; Daroini, Ahsin (Universitas Islam Kadiri, 2024)
This research aims to analyze the role of the financial services institution FIFGROUP in the Dhoho Kediri Airport area and its potential in supporting the achievement of Sustainable Development Goals (SDGs). The approach chosen in this research is a qualitative approach. The results indicate that FIFGROUP's role in supporting the local economy, particularly for small and medium enterprises (SMEs), is still not optimal and requires stronger branding and outreach. While the impact on poverty reduction and inequality has not been significant, FIFGROUP's programs hold great potential if loans are used for entrepreneurial activities. Moreover, there are positive indications in supporting gender equality, as women are able to actively participate in the family economy through business loans. Recommendations are made for FIFGROUP to expand its reach, provide assistance to customers, and strengthen partnerships with the government and local institutions to maximize its contribution to achieving the SDGs